2007
DOI: 10.1111/j.1939-1676.2007.tb03042.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors in Cats with Chronic Kidney Disease

Abstract: , and the BENRIC (benazepril in renal insufficiency in cats) Study Group Background: Chronic kidney disease (CKD) is a common cause of morbidity and mortality in cats. Hypothesis: Some baseline variables are associated with shorter survival times in cats with CKD. Animals: Client-owned cats. Methods: Cats with CKD with initial plasma creatinine concentration $2.0 mg/dL and urine specific gravity (USG) #1.025 were recruited into a prospective clinical trial that compared benazepril with a placebo. We describe b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
76
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(90 citation statements)
references
References 19 publications
11
76
0
3
Order By: Relevance
“…These tests were only run for two 25 week-old NP-C disease cats. Urine protein/creatinine ratio was normal (0.15 and 0.18; reference range <0.2) (15). Mild elevations in both pre-prandial (8.6 μmol/L and 22.0 μmol/L; reference <2.0 μmol/L) and post-prandial bile acids (18.4 μmol/L and 37.8 μmol/L; reference <10 μmol/L) were found.…”
Section: Resultsmentioning
confidence: 99%
“…These tests were only run for two 25 week-old NP-C disease cats. Urine protein/creatinine ratio was normal (0.15 and 0.18; reference range <0.2) (15). Mild elevations in both pre-prandial (8.6 μmol/L and 22.0 μmol/L; reference <2.0 μmol/L) and post-prandial bile acids (18.4 μmol/L and 37.8 μmol/L; reference <10 μmol/L) were found.…”
Section: Resultsmentioning
confidence: 99%
“…pCre is the most reliable marker for feline CKD, as described earlier [2], and its significance as a prognostic marker of feline CKD has been recently demonstrated [8]. Therefore, the degree of renal Ang II induction is not correlated with the severity of feline CKD, although Ang II induction may contribute to the progression of glomerulosclerosis.…”
Section: Discussionmentioning
confidence: 90%
“…In a prospective clinical trial, King et al [15] found a highly significant negative correlation between plasma P concentration and survival time. The relevance of serum P in CKD was further confirmed in a retrospective study on predictors of survival time: Boyd et al [16] found serum P concentration at time of diagnosis to be the only clinicopathologic variable tested that was predictive of survival.…”
Section: Discussionmentioning
confidence: 99%